On the Meaning of 'Europe' for Architectural History. Issue 1 (13th June 2018) - Nitzan-Shiftan, Alona; Stieber, Nancy
Abstract : This introduction to the special collection 'The Meaning of "Europe" for Architectural History' raises issues about the relationship between knowledge and geopolitics, in particular the significance of 'Europe' for the production of architectural knowledge.